2021
DOI: 10.3390/app11188432
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductivity and Dielectric Relaxation of NASICON Superionic Conductors at the Near-Cryogenic Regime

Abstract: With a crystal lattice structure first characterized in the 1970s, NASICON sodium-based superionic conductors have recently found renewed interest as solid electrolytes in sodium-ion and seawater flow batteries due to their exceptional ionic conductivity being on the same scale as liquid electrolytes. Since sodium ions in the crystal lattice move among interstitial positions through site-specific bottlenecks, the overall conductivity is strongly dependent on the NASICON composition. In this work, we report on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…The hump at 820 °C could be attributed to the conversion of low‐temperature monoclinic ZrO 2 to tetragonal [16] and the onset of NASICON conversion. The hump at 1050 °C might be correlated to crystallization of NASICON [17,18] . Upon investigation of the SS_NCO XRD patterns (Figure 4e) at different processing steps, it was observed that the reflections after the first mixing in the planetary ball mill were mainly from precursor materials predominantly ZrO 2 , implying that 24 h grinding with the mill achieved size reduction and mixing but little or no initial reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hump at 820 °C could be attributed to the conversion of low‐temperature monoclinic ZrO 2 to tetragonal [16] and the onset of NASICON conversion. The hump at 1050 °C might be correlated to crystallization of NASICON [17,18] . Upon investigation of the SS_NCO XRD patterns (Figure 4e) at different processing steps, it was observed that the reflections after the first mixing in the planetary ball mill were mainly from precursor materials predominantly ZrO 2 , implying that 24 h grinding with the mill achieved size reduction and mixing but little or no initial reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The hump at 1050 °C might be correlated to crystallization of NASICON. [17,18] Upon investigation of the SS_NCO XRD patterns (Figure 4e) at different processing steps, it was observed that the reflections after the first mixing in the planetary ball mill were mainly from precursor materials predominantly ZrO 2 , implying that 24 h grinding with the mill achieved size reduction and mixing but little or no initial reaction. After calcination at 700 °C for 12 h, ZrO 2 and intermediate NaZr 2 (PO 4 ) 3 NASICON reflections were observed.…”
Section: Particle Size Distribution and Surface Areamentioning
confidence: 99%
“…For the pristine Na 3 Zr 2 Si 2 PO 12, the sintered sample's ionic conductivity of 1.2 mS/cm at 60 • C is relatively high. [31][32][33] The total ionic conductivity of NASICON-based solid electrolytes depends on the density of the sample and hence its crystallinity, type of synthesis method, and grain boundaries present. Denser pellets are produced by sintering at higher temperatures and longer soaking time.…”
Section: Introductionmentioning
confidence: 99%
“…using the sol‐gel technique and spark plasma sintering. For the pristine Na 3 Zr 2 Si 2 PO 12, the sintered sample's ionic conductivity of 1.2 mS/cm at 60°C is relatively high 31–33 …”
Section: Introductionmentioning
confidence: 99%